Extensive air showers - Rao, M. V. S (World Scientific, 1998)
Includes bibliographical references and indexes.; This book describes the EAS phenomenology, the detectors and techniques used, and the latest results on the energy spectrum and composition of the primaries of EAS's and the results on high energy interactions obtained from EAS studies. It also describes the new TeV and PeV gamma ray astronomy (which has been developing over the past decade) and the newly emerging neutrino astronomy, which are related to the origin of cosmic rays.